Scripture as communication : introducing biblical hermeneutics - Brown, Jeannine K. (Grand Rapids, Michigan : Baker Academic, 2021)
Jeannine Brown, a seasoned teacher of biblical interpretation, believes that communication is at the heart of what happens when we open the Bible. We are actively engaging God in a conversation that can be life changing. In this guide to the theory and practice of biblical hermeneutics, Brown emphasizes the communicative nature of Scripture, proposing a communication model as an effective approach to interpreting the Bible. The new edition of this successful textbook has been revised and updated to interact with recent advances in interpretive theory and practice.
How to go about topical studies.
Includes bibliographical references and index.
Keywords: Bible -- Hermeneutics; Communication -- Religious aspects -- Christianity